DIGITAL FLIPBOOK KUMPULAN ANDEI-ANDEI SUKU MELAYU JERIENG BANGKA SEBAGAI UPAYA PEMERTAHANAN SASTRA LISAN DAN PENGGIATAN ECOLITERACY - Oktarina, Santi; Fikri, Muhammad Zakiul; Khoiriti, Inayah; Anastasya, Anastasya; Meida, Aghnia Misiarani; Qurniati, Rahmah (Fakultas Keguruan dan Ilmu Pendidikan Universitas Sriwijaya, 2024)
This research aims to develop a digital flipbook-based teaching material product in the form of a collection of andei-andei of the Jerieng Bangka Malay tribe as an effort to preserve oral literature and activate ecoliteracy. This research is a Research and Development (R&D) study with a modified model of Borg and Gall and Alessi and Trollip. The research data were obtained through interviews, questionnaires, and documentation techniques collaborated with ethnographic studies at the preliminary research stage.. The results of the needs analysis data show that andei-andei preservation is needed and can be developed or presented in the form of media in the form of digital flipbooks. The product produced through the design and development stage obtained a score of 95.83% for material feasibility assessment, 88.63% for language feasibility, and 93.75% for media/graphic feasibility. The results of the small group trial also showed that the product was feasible to use with an average score of 85.25.